Redu Cultural Elements and Characters of The Characters in the Play Novel Elephant Mada Oath in Manguntur Work Sky Kresna Hariadi - Sujoko Sujoko (Inovan Publisher, 2026)
The purpose of this research is to describe the cultural elements and the characters in the novel